One-pot synthesis of 5-hydroxymethylfurfural by cellulose hydrolysis over highly active bimodal micro/mesoporous H-ZSM-5 catalyst - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Thakur, Pratika; Sawant, Sanjay D.; Zambre, Vishal P.; Bokade, Vijay V. (ACS Sustainable Chemistry & Engineering, 2014)
Direct synthesis of 5-hydroxymethylfurfural (5-HMF), a useful renewable biofuel and biochemical, was systematically studied by hydrolysis of microcrystalline cellulose over Bimodal-HZ-5 zeolite. Bimodal-HZ-5 zeolite obtained by post-synthesis modification of H-ZSM-5 with desilication was found to be a potential heterogeneous catalyst with 67% cellulose conversion and 46% yield of 5-HMF. Bimodal-HZ-5 was observed to be reusable for four cycles, without any loss in activity. The detailed optimization of process parameters and catalyst reusability are also presented. The present study opens a new avenue for the renewable one-pot synthesis of 5-HMF, a valuable product.
Keywords: 5-Hydroxymethylfurfural; Biomodal-HZ-5; glucose; Hydrolysis; Microcrystalline cellulose